Pengaruh Model Pembelajaran Inkuiri Berbantuan PhET Simulation Terhadap Kemampuan Berpikir Tingkat Tinggi Siswa SMP dalam Pembelajaran IPA - David Akhyar Rosyady (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine students' higher-order thinking skills and to examine the effect of the inquiry learning model assisted by PhET Simulation on students' higher-order thinking skills in the topic of motion and force. This research employed a quantitative approach with a quasi-experimental design using a nonequivalent control group design. The sample consisted of two classes, namely an experimental class that received treatment using the inquiry learning model assisted by PhET Simulation and a control class that received conventional learning. Data were collected through tests in the form of pretest and posttest. The research instrument consisted of 10 multiple-choice questions developed based on higher-order thinking skills indicators. The data were analyzed using normality test, homogeneity test, and hypothesis testing with independent sample t-test. The results showed that students' higher-order thinking skills in the experimental class improved better than those in the control class. This was supported by the hypothesis testing result which showed a significance value of 0.005 < 0.05. Therefore, it can be concluded that there is a significant effect of the inquiry learning model assisted by PhET Simulation on students' higher-order thinking skills.
Finalisasi 1 Juli 2026_Yudi
Keywords: PhET Simulation; higher-order thinking skills; motion and force; Inquiry learning model